Hooch blindness: a community study report on a few indoor patients of toxic optic neuropathy following consumption of adulterated alcohol in West Bengal - Samanta, SK; Fariduddin, K; Mahapatra, N; Bhunia, J; Mondal, P (Nepalese Journal of Ophthalmology, 2012)
Introduction: Hooch blindness following consumption of adulterated alcohol has been known for centuries. Objective: To study cases of mass alcohol intoxication followed by Hooch blindness in eastern India. Materials and methods: Ten patients of toxic amblyopia collected from a community mass intoxication following consumption of adulterated alcohol were studied. The parameters studied were the findings of ocular examination, applanation tonometry, automated perimetry and visual-evoked potential (VEP). As a part of the special investigations fundus photography and OCT were done. Routine blood examination, fasting lipid profile, postprandial blood sugar estimation were done . All patients were treated with injections of methyl prednisolone and Hydroxy cobalamine, antioxidants and local neuro-protective agents. Results: Along with diminished vision (from NPL to 3/60), marked pallor of the disc without any other retinal change were noted. The amplitude on VEP was significantly reduced. However, visual improvement (up to 6/18) in 7 patients was observed within 6 weeks of treatment. Conclusion: Hooch blindness in India can be prevented by creating awareness among the target population and reducing the cost of country liquor. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5868 NEPJOPH 2012; 4(1): 162-164